The AudioGraph Web-based lecturing system : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Computer Science at Massey University, Palmerston North, New Zealand - Slusanschi, Horia Cristian (Massey University, 2004)
In recent years, the pace of technological development has grown tremendously. As a result, the half-life of knowledge has decreased from hundreds and tens of years to just a few years or even mere months in certain fields. In order to be able to adapt efficiently to this unprecedented wave of knowledge, organizations and individuals must adopt new ways of learning and training. Web-based education is a viable solution to the problem of quickly disseminating fresh knowledge as it emerges. However, one of the main challenges of effective web-based education remains the application of sound educational principles in the design and delivery of technology-enabled courses. Our primary aim has been to provide lecturers with an effective and easy to use system that would assist web-based teaching and learning, allowing them to focus on the application of relevant educational principles rather than requiring them to master arcane technical complexities. To enhance our perspective and better inform our design decisions, we explore the factors contributing to effective web-based education and examine a number of existing lecturing systems applicable to the development and distribution of educational content over the Web. We then investigate means of preparing and presenting educational content. We place particular emphasis on the guiding principles of human interface design that have permeated our work, and have contributed to the enhanced usability characteristics of our system. We then discuss the challenges of data compression and review the technologies we chose to help make our approach viable and efficient. In describing the software architecture of the system, we introduce the various design patterns that have helped our successful implementation gain robustness and flexibility, and discuss various tradeoffs encountered throughout the design and development of the system. Finally, we present the conceptual and technical conclusions we have reached and we briefly explore future avenues of research and indicate a number of particularly interesting and potentially fruitful areas.
Keywords: Computer-assisted instruction; Authoring programmes; Websites; Distance education; Computer-assisted instruction